2015
DOI: 10.7287/peerj.preprints.1105v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Workload assessment for mental arithmetic tasks using the task-evoked pupillary response

Abstract: Pupillometry is a promising method for assessing mental workload and could be helpful in the optimization of systems that involve human-computer interaction. The present study focuses on replicating the studies by Ahern (1978) and Klingner (2010), which found that for three levels of difficulty of mental multiplications, the more difficult multiplications yielded larger dilations of the pupil. Using a remote eye tracker, our research expands upon these two previous studies by statistically testing for each 1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Although the effects for the different physiological measures were mostly similar to each other and in the expected direction, each of these measures has unique strengths and weaknesses. For example, consistent with previous research in memory tasks and arithmetic tasks (e.g., Beatty, 1982;Klingner, 2010;Marquart & De Winter, 2015), pupil diameter has the advantage that it responds within a few tenths of second to changes in task demands, and that it can reach a peak dilation of 0.5 mm in as little as 1 s. It should be noted, however, that fluctuations in pupil diameter might be confounded by environmental lighting and gaze direction (e.g., Beatty, 1982;Klingner, 2010). The heart rate has lower temporal sensitivity, and therefore is less suitable for assessing the effect of scenarios.…”
Section: Hypothesis 2: Effects Of Time Pressure On Physiological Meassupporting
confidence: 89%
See 1 more Smart Citation
“…Although the effects for the different physiological measures were mostly similar to each other and in the expected direction, each of these measures has unique strengths and weaknesses. For example, consistent with previous research in memory tasks and arithmetic tasks (e.g., Beatty, 1982;Klingner, 2010;Marquart & De Winter, 2015), pupil diameter has the advantage that it responds within a few tenths of second to changes in task demands, and that it can reach a peak dilation of 0.5 mm in as little as 1 s. It should be noted, however, that fluctuations in pupil diameter might be confounded by environmental lighting and gaze direction (e.g., Beatty, 1982;Klingner, 2010). The heart rate has lower temporal sensitivity, and therefore is less suitable for assessing the effect of scenarios.…”
Section: Hypothesis 2: Effects Of Time Pressure On Physiological Meassupporting
confidence: 89%
“…Their findings showed that participants, regardless of their level of driving experience, narrowed their gaze distribution when the driving speed was increased. Recently, remote eye trackers have shown to be promising tools for measuring the pupil dilation response as a function of cognitive task demands in low-cost measurement setups (Klingner, Kumar, & Hanrahan, 2008;Marquart & De Winter, 2015) as well as in driving simulators (Palinko, Kun, Shyrokov, & Heeman, 2010).…”
Section: Previous Research That Investigated the Effects Of Time Presmentioning
confidence: 99%
“…The human pupil dilates during effortful cognitive activities such as those that require increasing of deployed attentional control resources (Chen & Epps, 2014; Kursawe & Zimmer, 2015; Laeng et al, 2011; Lisi et al, 2015; Marquart & de Winter, 2015; Meghanathan et al, 2014). For example, maintaining information in working memory (WM) is accompanied by subjectively noticeable cognitive effort, and an increase in memory set size and cognitive effort is associated with pupil dilation during WM tasks (Heitz et al, 2007; Kahneman & Beatty, 1966; Karatekin et al, 2004; Klingner et al, 2011; Unsworth & Robison, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Pupil dilation can be used as a peripheral indicator of brain noradrenergic activity and mental workload in a testing situation. The measurement of pupil diameter has been deemed a promising method for assessing mental workload 38 , 43 , 44 . Task-evoked pupillary responses (TEPRs) have been suggested for exploring the inherent relationship between a task and pupillary dilation 44 .…”
Section: Methodsmentioning
confidence: 99%